The Relationship of Toddler Visits with the Government (SAMBAL MATAH) on Toddler Visits to POSYANDU - Nur Fitriah; Ni Nyoman Murti; Endah Wijayanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Posyandu activities can prevent malnutrition, currently visits to posyandu are still low where visits to posyandu have only reached 62.16%, so efforts are made for government involvement to increase visits to posyandu with the SAMBAL MATAH innovation, namely Visit Toddlers with the Government, government involvement in posyandu activities are very important to increase visits to posyandu. This type of research uses a quasy experimental research design, namely pre post-test with control group design. The population in this study were all mothers with toddlers of 93 people with a purposive sampling sample, as many as 17 people in the experimental group and 17 people in the control group. The measuring tool uses attendance documentation data from the posyandu and the MCH handbook. Data analysis used the Mann Whitney test. Visits to the posyandu before the intervention 100% did not visit and after the intervention 94.1% visited the posyandu. Visits to the posyandu before the WA Group conducted 100% did not visit and after the WA Group 11.7% visited the Posyandu. There is a relationship between SAMBAL MATAH activities and visits to posyandu for mothers with toddlers in the Work Area of the Handil Baru Health Center, Tanjung Harapan Village, with a p value of 0.000. Government involvement in supporting posyandu activities can provide motivation for mothers who have toddlers to bring their toddlers to posyandu because SAMBAL MATAH activities apart from providing motivation also provide information about the importance of posyandu activities